2002
DOI: 10.1089/089277902761403005
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopy-Assisted Orchidopexy: An Ideal Treatment for Children with Intra-Abdominal Testes

Abstract: Laparoscopic orchidopexy is the logical extension of diagnostic laparoscopy for the evaluation of NPT. Concerning the technique, we believe that LAO with intact spermatic vessels could be considered the treatment of choice in the patient with IAT, as it does not affect normal testicular vascularization. Alternatively, in the case of very high IAT (more than 3 cm from IIR), an FS procedure may be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 25 publications
0
16
0
1
Order By: Relevance
“…The diagnostic laparoscopy is undoubtedly more suitable for identifying the different anatomic conditions: blind ending cord structures (20%), cord elements entering the internal inguinal ring (45%), testis agenesis (2%), or an intraabdominal testis (33%) [7,12]. With respect to the most suitable operative technique for intraabdominal testis, most authors prefer the Fowle-Stephens procedure.…”
Section: Cryptorchidism With Nonpalpable Testismentioning
confidence: 99%
See 3 more Smart Citations
“…The diagnostic laparoscopy is undoubtedly more suitable for identifying the different anatomic conditions: blind ending cord structures (20%), cord elements entering the internal inguinal ring (45%), testis agenesis (2%), or an intraabdominal testis (33%) [7,12]. With respect to the most suitable operative technique for intraabdominal testis, most authors prefer the Fowle-Stephens procedure.…”
Section: Cryptorchidism With Nonpalpable Testismentioning
confidence: 99%
“…During the first step, the inner spermatic vessels are clipped 4-cm away from the testis. After an interval of 3 to 6 months, which are necessary for the development of collateral vascularization deriving from the deferential vessels, the second step is performed by sectioning the inner spermatic vessels and performing the orchidopexy via the internal inguinal ring or a neoring created medially to the epigastric vessels [12].…”
Section: Cryptorchidism With Nonpalpable Testismentioning
confidence: 99%
See 2 more Smart Citations
“…On removing the ports , hemostasis should also be assessed at the port sites, as well as being sure that the umbilical closure does not include bowel or omentum . Esposito et al 36 reported their experience with diagnostic laparoscopic in 85 children with nonpalpable testes, of whom 25 children had intra-abdominal testes. In 24 children laparoscopic orchidopexy was successful.…”
Section: Laparoscopic Orchidopexymentioning
confidence: 99%